How to calculate sample size in animal and human studies - Zhang, Xinlian; Hartmann, Phillipp (Frontiers in Medicine, 2023)
One of the most important statistical analyses when designing animal and human studies is the calculation of the required sample size. In this review, we define central terms in the context of sample size determination, including mean, standard deviation, statistical hypothesis testing, type I/II error, power, direction of effect, effect size, expected attrition, corrected sample size, and allocation ratio. We also provide practical examples of sample size calculations for animal and human studies based on pilot studies, larger studies similar to the proposed study—or if no previous studies are available—estimated magnitudes of the effect size per Cohen and Sawilowsky.